Penerapan ERP Berbasis ODOO pada Studi Kasus Apotek Handal Modul Point of Sale - Ziveria, Mira; Ilham Maududi (KALBISCIENTIA Jurnal Sains dan Teknologi, 2025)
In this study, the researchers will discuss the application of ERP based on Odoo on the Handal Pharmacy. the problem that occurs is the order that is still injected manually, often the loss of data in the recording in the accounting. The Odoo module is the point of sale. This research aims to implement the point of sale odoo system on Handal Pharmacy to solve the problem. The type of research that uses qualitative methods by collecting data from interviews and observations. This research uses the ASAP method to help design ERP implementations. The result of this study is the point of sale system in the Handal Pharmacy. Keywords: : Pharmacy, ERP ,Odoo, ASAP